Towards a more holistic understanding of lecturers' perspective of learning management systems at a South African university - Ndobe, Tsakani Violet (My University, 2018)
The integration of technology into an educational context is advocated by many as a means of preparing students to cope with the current information society, as well as enhance pedagogical practices and knowledge transmission. One way to integrate technology within educational contexts is through Learning Management Systems (LMS). LMS integration approaches include learning material repositories, discussion boards, blogs, messaging, and chat rooms. While many research studies have focused on the role that students play in the successful use of the LMS, use of LMS by lecturers and the potential benefits that may be accrued as a result of making use of the LMS, have not yet been fully explored. The apparent limited use of LMS in Sefako Makgatho Health Sciences University (SMU) in South Africa provided the impetus for this qualitative case study in order to develop an in-depth, holistic understanding of LMS use and non-use by SMU lecturers. Data was collected via semi-structured interviews with SMU lecturers. The Unified Theory of Acceptance and Use of Technology (UTAUT) framework was used as a lens for the data analysis. Findings indicate that SMU lecturers’ decisions to make use or not to make use of the LMS are being influenced by performance benefits (PE) such as communication, assessment, content upload, anytime-anywhere teaching and learning, management of large classes, student management of learning and lecture delivery. In relation to effort (EE), findings suggest that to make use of LMS initial training, continual practice, organisational support, and ease-of-use are essential. Furthermore, social influences (SI) appear to be important with colleagues, the organisation as well as students playing a role in decision around LMS use. Findings for facilitating conditions (FC) indicate that conditions of training need to be improved, organisational support must be more available and the technology infrastructure necessary to use the LMS must be sufficient. Student resistance, lack of refresher courses, extra work required to make effective use of the LMS, non-standardisation of LMS usage, limited infrastructure, and stable internet access were identified as limitations hindering the effective use of LMS.
This research report is submitted in partial fulfilment of the requirements for the degree of Master of Commerce (Information Systems) coursework in the University of the Witwatersrand (Wits), Johannesburg.
Keywords: Internet in education; Educational technology--South Africa; Computer-assisted instruction--South Africa